Students taking charge in grades K-5 : inside the learner-active, technology-infused classroom - Sulla, Nancy, author (New York, NY : Routledge, 2019)
Discover how to design innovative learning environments that increase student ownership so they can achieve at high levels and meet rigorous standards. Students Taking Charge shows you how to create student-driven classrooms that empower learners through problem-based learning and differentiation, where students pose questions and actively seek answers. Technology is then used seamlessly throughout the day for information, communication, collaboration, and product generation
Introduction -- The why for your instructional design journey -- Engaging students through a core problem to solve -- Engaging students through clearly articulated expectations -- Engaging students through differentiated learning activities -- Empowering students to take responsibility for their learning -- Promoting efficacy through facilitation of learning -- Physical classroom design -- Principles and paradigm shifts -- Special considerations
Includes bibliographical references and index
Keywords: Student-centered learning; Active learning; Effective teaching; Classroom environment